A propósito de la formalización de los fenómenos físicos: un análisis desde la perspectiva newtoniana - Ospina Ramírez, Andrés; Tobón Cardona, Érika; Aguilar Mosquera, Yirsen (Revista Científica, 2011)
The study of the processes of formalization of physical phenomena yields guidelines for science education, can somehow clarify the physical-mathematical relationship and the role of experimentation in science learning. In this regard it is argued that the analysis of the processes of formalization of the theory of color and light propagation carried out by Newton and some students in particular socio-cultural contexts, can not only explain such a relationship but allows the approach educational alternatives in the teaching of physics. As a proposal is made a characterization of the formalization process which highlights the organization of experience, characterization and quantification, the role ofexperimentation, mathematization, and the processes of socialization. It contrasts the thinking and formalize the phenomenon of light and color developed by Newton and some students, from which it is theorized and creating a path for the formalization of physical phenomena. Finally, as an alternative to teaching, these components are configured with a proposal for intervention in the classroom, where the goal is not to acquire a wealth of scientific knowledge but to develop formalized processes for students and teachers from specific actions such as: design measurement methods, identify attributes, perform, link variables, compare results, deduce laws, compare ideas, among others.